2018
DOI: 10.1016/j.ymthe.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy-Induced Antigen-Specific Tregs Inhibit Neuro-inflammation and Reverse Disease in a Mouse Model of Multiple Sclerosis

Abstract: The devastating neurodegenerative disease multiple sclerosis (MS) could substantially benefit from an adeno-associated virus (AAV) immunotherapy designed to restore a robust and durable antigen-specific tolerance. However, developing a sufficiently potent and lasting immune-regulatory therapy that can intervene in ongoing disease is a major challenge and has thus been elusive. We addressed this problem by developing a highly effective and robust tolerance-inducing in vivo gene therapy. Using a pre-clinical ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 54 publications
(79 reference statements)
2
66
0
Order By: Relevance
“…This result is compatible with a qualitative alteration of CD4 + T cells and with the fact that liver-based tolerance induction to FIX confers transferable tolerogenic properties to the CD4 + T cell compartment (31). Moreover, it was recently shown that liver expression of an autoantigen is able to induce autoantigen-specific regulatory T cells (Tregs), protecting mice from neuroinflammation in 2 models of multiple sclerosis (48,49). In addition, it was found that rAAV hepatocytes' transduction of MHCI molecule H2-K d conditions C57BL/6 mice for successful transplantation of fully allogenic H2-K d pancreatic islets because of local liver expansion of a subset of PD-1 + CD8 + T cell-harboring regulatory functions (50).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This result is compatible with a qualitative alteration of CD4 + T cells and with the fact that liver-based tolerance induction to FIX confers transferable tolerogenic properties to the CD4 + T cell compartment (31). Moreover, it was recently shown that liver expression of an autoantigen is able to induce autoantigen-specific regulatory T cells (Tregs), protecting mice from neuroinflammation in 2 models of multiple sclerosis (48,49). In addition, it was found that rAAV hepatocytes' transduction of MHCI molecule H2-K d conditions C57BL/6 mice for successful transplantation of fully allogenic H2-K d pancreatic islets because of local liver expansion of a subset of PD-1 + CD8 + T cell-harboring regulatory functions (50).…”
Section: Discussionsupporting
confidence: 59%
“…Both preexisting humoral responses and CD8 + and CD4 + T cell responses were affected by dual muscle-liver transgene expression, with transgene-specific CD8 + T cells undergoing retention and/or depletion and exhaustion and transgene-specific CD4 + T cells remaining present but unable to boost antibody production. These CD4 + T cells are presumably forming a pool of cells able to undergo conversion into Foxp3 + Tregs, as evidenced in multiple sclerosis models (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs play an essential role in tolerance induction after liver gene transfer as demonstrated by the increased transgene immunogenicity observed after Tregs depletion (60,89,92,106). Consistently, increased Tregs expansion by rapamycin treatment, favored the induction of liver-mediated tolerance even in the presence of pre-existing anti-transgene immunity (107,108). Other mechanisms like the induction of CD8 + regulatory T cells (109), the degradation of T cells in hepatocytes (110), and the CD4 + T cell anergy (111) were proposed in the establishment and maintenance of liver tolerance.…”
Section: Immune Responses Against the Transgene Productmentioning
confidence: 88%
“…Although widely used as vector systems for liver directed in vivo gene therapy, few groups explored the use of AAV to induce tolerance to autoAgs in autoimmune diseases. Liver gene therapy with an AAV vector encoding for the full sequence of myelin oligodendrocyte glycoprotein (MOG) prevented development of and reversed preexisting EAE via the induction/expansion of Ag-specific FoxP3 + Tregs ( 58 ). Earlier studies of intramuscular injection in NOD mice of AAV encoding for glutamic acid decarboxylase (GAD) peptides prevented the development of overt diabetes in NOD mice via skewing of Teff cells to Th2 responses, but those studies were not further developed and active tolerance was not demonstrated ( 59 ).…”
Section: Cell Free Strategiesmentioning
confidence: 99%